Analysis of Spatial Planning in the Tourism Destination of Taman Eden 100, Lumban Julu District, Toba Regency - Daniel Sihombing (Politeknik Pariwisata Medan, 2021)
Eden Park 100 which is located in Lumban Julu District, Toba Regency, North Sumatra Province. Has various kinds of natural tourism potential attractions, especially plant and forest conservation. There are indications of factors that influence the development of regional spatial patterns with tourism destinations. The development of a forest conservation area is not only related to the natural environment but with the use of pine resin for economic consumption resulting in a conflict of interest. This spatial change is caused by massive economic activities that occupy spaces in the area. From the description above, the aim of this research is to provide zoning directions in the Eden Park 100 Tourism Destinations area. This study describes the identification of the direction of planning and development of spatial management. Data collection is carried out through primary data collection and secondary data, where primary data collection is carried out by means of observation, interviews and questionnaires to add information. Secondary data were obtained. from agencies and agencies related to this research, including from the Forestry Service of Toba Regency. Single case study method to explore this research. The data were analyzed using descriptive qualitative analysis. The results of the questionnaire were then analyzed by giving weight and rating to each criterion. Weights are assigned a value ranging from 4 (very important), 3 (important), 2 (not important), 1 (very insignificant). Meanwhile, the rating is determined based on the number of respondents who choose certain criteria in the SWOT analysis questionnaire. The end of this research is the zoning direction in the area of ​​Eden Park 100 tourist destinations to control development so that it remains consistent with existing spatial planning regulations.